2005
DOI: 10.1017/s095026880500470x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis E virus (HEV) antibody and the possible association with chronic liver disease: a case-control study in Albania

Abstract: A case-control study involving 109 in-patients with chronic liver disease and 190 in-patients with no apparent liver disease was conducted to evaluate the seroprevalence of anti-HEV antibodies and the possible association with chronic liver disease. Among cases, the anti-HEV prevalence was 36.6% which increased significantly by age; among controls, the prevalence was 12.1% (P<0.05) and was similar among age groups <60 years. Among cases, aged >50 years (OR 4.0, 95% CI 1.4-11) and the presence of end stage live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
6
18
0
1
Order By: Relevance
“…Trichuris trichiura and Giardia duodenalis were the intestinal parasites most frequently found [20]. The prevalence of hepatitis E virus (HEV) antibodies was found to range from 8% to 12% in selected groups of the Albanian general population [19,21,22]. The faeco-oral route is supported by studies that have found a correlation between the consumption of vegetables irrigated with contaminated water and H. pylori [23] and by studies, sometimes with conflicting results, showing an association between the prevalence of H. pylori and HAV antibodies [24][25][26][27].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Trichuris trichiura and Giardia duodenalis were the intestinal parasites most frequently found [20]. The prevalence of hepatitis E virus (HEV) antibodies was found to range from 8% to 12% in selected groups of the Albanian general population [19,21,22]. The faeco-oral route is supported by studies that have found a correlation between the consumption of vegetables irrigated with contaminated water and H. pylori [23] and by studies, sometimes with conflicting results, showing an association between the prevalence of H. pylori and HAV antibodies [24][25][26][27].…”
Section: Discussionmentioning
confidence: 98%
“…Also, in this country, the emerging epidemiological pattern of H. pylori infection seems to be very similar to that for other infections spread by the fecal-oral route. Seroepidemiological studies have shown that the [17][18][19]. The prevalence of intestinal parasites in apparently healthy Albanian individuals was reported to be 24%.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, in addition to HCV infection, mixed infection (co-infection or superinfection) with HEV might have important significance in the emergence of these situations [40] . In recent years several studies reported that a great proportion (up to 44%) of patients with chronic liver disease were at risk of developing superinfection with HEV in highly endemic re-gions, which led further to hepatic decompensation with high morbidity and mortality [12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently some studies have reported a high prevalence of HEV infection in patients with chronic liver disease and others have suggested that superinfection with HEV in patients with underlying chronic liver disease can cause severe hepatic decompensation [12][13][14][15][16][17] . Bayram The present study was conducted to investigate the prevalence of superinfection of HEV in patients with chronic hepatitis B and chronic hepatitis C infections living in Gaziantep, a city located in the southeastern part of Turkey with 1.5 million inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, anti-HEV IgG is present in significant proportion among volunteer blood donors in endemic countries: 7.8% in Iran [Taremi et al, 2007]; 12.1% in Albania [Kondili et al, 2006]; 16.9% in Saudi Arabia [Abdelaal et al, 1998]; 43% in China ; and 45.2% in Egypt [Abdelhady et al, 1998]. Also, in certain geographic areas of the United States, it has been reported that the prevalence of anti-HEV IgG among volunteer blood donors varied from 18% to 21.3% Thomas et al, 1997;Meng et al, 2002].…”
Section: Volunteer Blood Donorsmentioning
confidence: 99%